Lung ultrasound in children and adolescents with long-term effects of COVID-19: Initial results - Gräger, Stephanie; Pfirschke, Rosalie; Lorenz, Michael; Vilser, Daniel; Krämer, Martin; Mentzel, Hans-Joachim; Glutig, Katja (Frontiers in Pediatrics, 2023)
Introduction Chronic health effects following acute COVID-19 are increasingly observed as the pandemic continues and are grouped under long COVID. Although the acute course of the COVID disease is often milder, long COVID also affects children and adolescents. As the symptoms present in Long-COVID often seem to be non-specific and not limited to organ systems, clarification of the causes and the creation of a meaningful, efficient and targeted diagnostic algorithm is urgently needed. Methods Therefore, in this prospective observational study, we examined 30 children with long COVID using lung ultrasound and compared the results with those of 15 lung-healthy children. Results In our study, no significant difference was found between the two groups in the morphological criteria of lung ultrasound of the pleura or pleural lung structures. There was no significant correlation between the lung ultrasound findings and clinical Data. Discussion Our findings are congruent with the current, albeit sparse, data. It is possible that the causes of persistent thoracic symptoms in long COVID might be more likely to be present in functional examinations, but not morphologically imageable. Nonspecific symptoms do not appear to be due to changes in the lung parenchyma. In conclusion, lung ultrasound alone and without baseline in acute disease is not suitable as a standard in the follow-up of long COVID patients. Further investigations on the morphological and functional changes in patient with long COVID is needed.